ADAMTS12, a new candidate gene for pediatric stroke - Witten, Anika; Rühle, Frank; de Witt, Marlous; Barysenka, Andrei; Stach, Michael; Junker, Ralf; Nowak-Göttl, Ulrike; Stoll, Monika (PloS one, 2020)
We recently reported a family-based genome wide association study (GWAS) for pediatric stroke pointing our attention to two significantly associated genes of the ADAMTS (a disintegrin and metalloproteinase with thrombospondin motifs) gene family ADAMTS2 (rs469568, p = 8x10.sup.-6) and ADAMTS12 (rs1364044, p = 2.9x10.sup.-6). To further investigate these candidate genes, we applied a targeted resequencing approach on 48 discordant sib-pairs for pediatric stroke followed by genotyping of the detected non-synonymous variants in the full cohort of 270 offspring trios and subsequent fine mapping analysis. We identified eight non-synonymous SNPs in ADAMTS2 and six in ADAMTS12 potentially influencing the respective protein function. These variants were genotyped within a cohort of 270 affected offspring trios, association analysis revealed the ADAMTS12 variant rs77581578 to be significantly under-transmitted (p = 6.26x10.sup.-3) to pediatric stroke patients. The finding was validated in a pediatric venous thromboembolism (VTE) cohort of 189 affected trios. Subsequent haplotype analysis of ADAMTS12 detected a significantly associated haplotype comprising the originally identified GWAS variant. Several ADAMTS genes such as ADAMTS13 are involved in thromboembolic disease process. Here, we provide further evidence for ADAMTS12 to likely play a role in pediatric stroke. Further functional studies are warranted to assess the functional role of ADAMTS12 in the pathogenesis of stroke.